Spurious Radiation Suppression in Microstrip Monopulse Antenna - Hnesh, Allaeldien Mohamed G (Eastern Mediterranean University EMU, 2017)
The monopulse technique has been widely used for target detection in Radar Tracking Systems. Various modern technologies have been used to implement it. The use of microstrip technology in the monopulse technique attracted a lot of researchers due to the light weight and the ability to integrate the antenna with the monopulse processing network in one structure. In most of the implementations the effect of monopulse processing network on the antenna performance is not considered. In this work, a novel shielding method is proposed to isolate the feed network form the system without loss of compactness. The proposed method might be used in different applications however special emphasis is given to the monopulse systems. A study has been carried out using the full wave Microwave Simulation software CST to demonstrate the efficiency of the shielding method, as well as a comparison between the planer monopulse shielded system and the conventional planer system. The design frequency was chosen to be 3GHz and the commercial FR-4 substrate was used. The final designed array was further improved by using a non-rectangular distribution, to reduce the minor lobes due to the planar array nature. The improved design exhibited difference nulls exactly at zero with depths about -23dB, the sum pattern maximum directivity was 18.4 dBi with sidelobes less than -23dB in E and H- planes. Due to the suppression of the feed network radiation the patterns of the proposed design were much more symmetrical than conventional monopulse arrays with deeper nulls. Keywords: Monopulse antenna, microstrip arrays, spurious radiation, feed network shielding, null depth.

ÖZ: Tek darbe tekniği, Radar İzleme Sistemlerinde sinyal algılaması için yaygın olarak kullanılan bir yöntemdir. Günümüze kadar bu tekniği uygulamak için çeşitli modern teknolojiler kullanılmıştır. Bu teknik, mikro şerit teknolojisinin kullanımı, antenin tek darbe işleme ağına tek bir yapıda entegre edilmesi ve hafifliği nedeniyle bir çok araştırmacıyı cezbetmiştir. Uygulamaların çoğunda, tek darbe işleme ağının anten performansına etkisi göz önüne alınmaz. Bu çalışmada, sistemin besleme ağını yalınlaştırmak için yeni bir koruyucu yöntem önerilmektedir. Önerilen yöntem tek darbe sistemleri için özel tasarlanmış olmasına rağmen farklı uygulamalarda da kullanılması mümkündür. Koruyucu yöntemin verimliliğini göstermek için tam dalga Mikrodalga Benzetim yazılımı (CST) kullanılarak bir çalışma gerçekleştirilmiş ve tek darbe korumalı sistem ile geleneksel düzlemsel sistem arasında karşılaştırma yapılmıştır. Tasarım frekansı 3 GHz, tasarım malzemesi de FR- 4 seçilmiştir. Son anten tasarımı, düzlemsel dizi niteliğinden dolayı meydana gelen küçük lobları azaltmak için dikdörtgen olmayan bir dağılım kullanarak daha da geliştirilmiştir. Geliştirilmiş tasarım, -23 dB'lik boşluk derinliği ile tam sıfır açısında derinlik sergilemektedir; toplam örüntü maksimuma yönelme 18.4 dBi ile E- ve Hdüzlemlerinde yan loblar -23 dB'den daha azdır. Besleme ağı radyasyonunun bastırılmasından ötürü, önerilen tasarımın hüzmeleri, geleneksel tek darbe dizilerinden çok daha simetriktir ve boşluk derinliği daha fazladır. Anahtar Kelimeler: Tek darbe anten, mikroşerit dizi, yapay radyasyon, besleme ağı yalınlaştırması, boşluk derinliği.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Supervisor: Assist. Prof. Dr. Rasime Uyguroğlu.
Keywords: Electrical and Electronic Engineering; Antennas (Electronics); Broadband communication systems; Monopulse antenna; microstrip arrays; spurious radiation; feed network shielding; null depth